Effects of hybridization on pelvic morphology: A macaque model. Issue 159 (October 2021) - Buck, Laura T.; Katz, David C.; Ackermann, Rebecca Rogers; Hlusko, Leslea J.; Kanthaswamy, Sree; Weaver, Timothy D.
Abstract: Ancient DNA analyses have shown that interbreeding between hominin taxa occurred multiple times. Although admixture is often reflected in skeletal phenotype, the relationship between the two remains poorly understood, hampering interpretation of the hominin fossil record. Direct study of this relationship is often impossible due to the paucity of hominin fossils and difficulties retrieving ancient genetic material. Here, we use a sample of known ancestry hybrids between two closely related nonhuman primate taxa (Indian and Chinese Macaca mulatta ) to investigate the effect of admixture on skeletal morphology. We focus on pelvic shape, which has potential fitness implications in hybrids, as mismatches between maternal pelvic and fetal cranial morphology are often fatal to mother and offspring. As the pelvis is also one of the skeletal regions that differs most between Homo sapiens and Neanderthals, investigating the pelvic consequences of interbreeding could be informative regarding the viability of their hybrids. We find that the effect of admixture in M. mulatta is small and proportional to the relatively small morphological difference between the parent taxa. Sexual dimorphism appears to be the main determinant of pelvic shape in M. mulatta . The lack of difference in pelvic shape between Chinese and Indian M. mulatta is in contrast to that between Neanderthals and H. sapiens, despite a similar split time (in generations) between the hybridizing pairs. Greater phenotypic divergence between hominins may relate to adaptations to disparate environments but may also highlight how the unique degree of cultural buffering in hominins allowed for greater neutral divergence. In contrast to some previous work identifying extreme morphologies in first- and second-generation hybrids, here the relationship between pelvic shape and admixture is linear. This linearity may be because most sampled animals have a multigenerational admixture history or because of relatively high constraints on the pelvis compared with other skeletal regions.